CODE-SWITCHING USED BY STUDENTS IN A SPEAKING CLASS ACTIVITY (The Case at Dian Nuswantoro University Semarang) - Fitriyani, Irul Dwi (Universitas Negeri Semarang, 2013)
This study is aimed to investigate which types of code switching, to figure out some functions of code switching and to reveal the factors that cause an increasing use of code-switching used by the students. The study belonged to a descriptive qualitative research. The result indicated that the total occurrences of code-switching generated by the 13 students are 73 times. For intra-sentential code-switching, it was found 39 utterances or 53.42% and for inter-sentential code-switching, it was found 34 utterances or 46.58%. Â The most significant function of code-switching is that to emphasize the message which totally holds the highest percentage: 32.05%. The most significant factor of code-switching is that repetition used for clarification which totally holds the highest percentage: 34.25%. Finally, it can be concluded that repetition used for clarification was the most significant factor which causes the occurrence of code-switching. This factor was likely to happen because it was generated to avoid misunderstanding and to add emphasis.